Economic performance of variable structure control: A case study - Figueroa, Jose Luis (2000)
The operating point of a chemical process is usually computed by optimizing a steady-state objective function, e.g. the profit, subject to the steady-state characteristics of the plant. However, the resulting point typically lies in the boundary of the operating region. The presence of disturbances can easily cause constraint violations in the transient. Thus, it is necessary to move the operating point away from the active constraints into the feasible region. The magnitude of this back-off has a direct influence on the economic side. The purpose of this paper is to study the effect of the combination of a state-observer and controller designed using structure variable techniques at the economical level of the process control.